2013
DOI: 10.1074/jbc.m113.527531
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Sirtuin 1 Deacetylates IRF1 Protein and Programs Dendritic Cells to Control Th17 Protein Differentiation during Autoimmune Inflammation

Abstract: Background:The roles of Sirt1 in regulating dendritic functions are not known. Results: Sirt1 deacetylates the IRF1 transcription factor to suppress IL-27 expression in dendritic cells, leading to elevated Th17 differentiation for inflammatory disease development. Conclusion: Sirt1 programs DC functions to promote Th17 differentiation and inflammation. Significance: This study defines a previously unappreciated inflammatory role of Sirt1 in dendritic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 48 publications
2
56
0
Order By: Relevance
“…The lack of SIRT1 in DCs reduced critical cytokine production, including IFNβ and IL-12, which we suggest contributed to a pathological Th2/Th17 immune response within the airways. Previous studies examining DC-specific KO mice reported no changes in DC maturation, differentiation, or development compared to WT DCs (39, 40), in agreement with our observations. Thus, our data indicate that SIRT1 has a unique role in modulating DC cytokine production in the context of a viral infection, such as RSV (12).…”
Section: Discussionsupporting
confidence: 93%
“…The lack of SIRT1 in DCs reduced critical cytokine production, including IFNβ and IL-12, which we suggest contributed to a pathological Th2/Th17 immune response within the airways. Previous studies examining DC-specific KO mice reported no changes in DC maturation, differentiation, or development compared to WT DCs (39, 40), in agreement with our observations. Thus, our data indicate that SIRT1 has a unique role in modulating DC cytokine production in the context of a viral infection, such as RSV (12).…”
Section: Discussionsupporting
confidence: 93%
“…In muscle cells, activation of the AMP/ATP sensor AMP kinase (AMPK) results in increased NAD + /NADH ratios and sirtuin 1 (SIRT1) activation 116 , resulting in deacetylation of PGC1α and promotion of metabolic pathways that restore NAD + /NADH ratios. In dendritic cells (DCs), SIRT1 mediates the deacetylation of interferon (IFN)-regulatory factor 1 (IRF1) and, in doing so, inhibits the ability of cells to produce interleukin-27 (IL-27) and IFNβ 117 . SIRT1 has also been reported to regulate the balance of IL-12p70 versus IL-23 production 118 and to repress PPARγ activity in DCs 119 .…”
Section: Signalling By Intracellular Metabolites In Dcsmentioning
confidence: 99%
“…Genetic polymorphisms of histone-modifying genes can also cause dysfunction of these genes and aberrant histone modifications (114116), which may further results in AITD. Sirtuin1 (SIRT1) is a class 3 nicotinamide adenine dinucleotide-dependent HDAC, which is intensively associated with immune response and autoimmune diseases (114116).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%
“…Sirtuin1 (SIRT1) is a class 3 nicotinamide adenine dinucleotide-dependent HDAC, which is intensively associated with immune response and autoimmune diseases (114116). A case–control study by Sarumaru et al reported that rs3758391 and rs4746720 in the SIRT1 gene were associated with higher levels of thyroid autoantibodies in AITD patients (117).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%